The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/1078390316657872
|View full text |Cite
|
Sign up to set email alerts
|

Nasogastric Tube Feeding for Individuals With Anorexia Nervosa

Abstract: NG feeding promotes short-term weight gain; however, long-term outcomes are poorly understood. Future research, using rigorous methods, is still needed to inform practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 65 publications
(128 reference statements)
1
17
0
1
Order By: Relevance
“…A 2014 review of 7 observational studies with children and adolescents found relatively increased in‐treatment weight gain, as well as caloric intake, with NG nutrition. A 2016 review of 19 refeeding studies (including 2 RCTs) found increased short‐term weight gain with NG nutrition compared with OO intake. Finally, another 2016 review of various refeeding approaches for patients with AN, including 10 studies incorporating supplemental NG nutrition into meal‐based methods, found that NG feeding was useful for increasing caloric intake.…”
Section: Discussionmentioning
confidence: 99%
“…A 2014 review of 7 observational studies with children and adolescents found relatively increased in‐treatment weight gain, as well as caloric intake, with NG nutrition. A 2016 review of 19 refeeding studies (including 2 RCTs) found increased short‐term weight gain with NG nutrition compared with OO intake. Finally, another 2016 review of various refeeding approaches for patients with AN, including 10 studies incorporating supplemental NG nutrition into meal‐based methods, found that NG feeding was useful for increasing caloric intake.…”
Section: Discussionmentioning
confidence: 99%
“…Our literature review found various narrative reviews concerning somatic aspects of AN, but only a few recent systematic reviews concerning multi-organic somatic medications. In fact, most systematic reviews are concerned with the effects of weight gain or pharmacological treatments (hormone replacement, biphosphonates, teriparatide, and vitamin K) on bone mineral density and secondary osteoporosis [39,44,49,50] or they concerned nutritional therapeutic modalities and their impact on weight changes [42,46], or the efficacy of nasogastric enteral nutrition and adverse effects [47,52,53]. Most of the studies involved small samples, with heterogeneity within and among studies concerning evaluations, biomarkers and age range, with heterogeneous adolescent and adult populations, and various durations, often with an insufficient follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…One systematic review [47] including 18 studies and 1427 adolescent and adult AN patients (1406 F/21 M), evaluated physiological and psychiatric outcomes and patient adherence to nasogastric feeding (NG). It can be noted that 95% of the studies were conducted in inpatient medical or psychiatric units and only one study concerned ambulatory patients [109].…”
Section: Resultsmentioning
confidence: 99%
“…In restrictive eating disorders where patients are underweight, therapists may insist on weight gain at all costs, including strategies for intensive nutritional rehabilitation such as nasogastric tube feeding that involves no behavioral learning and may actually impede such learning. A review of the efficacy of tube feeding in AN suggests that short-term weight gain is generally achieved without concurrent improvement in psychiatric symptoms or evidence of long-term sustainability ( Kells and Kelly-Weeder, 2016 ). A comparison of feeding methods in anorexia found no advantage in efficacy for tube feeding over ordinary oral intake of food or liquid supplements, and a wide range of disadvantages ( Hart et al, 2013 ).…”
Section: A Feedback Model Of Eating Disorders: Mind Body and Behavimentioning
confidence: 99%